2014
DOI: 10.1186/1471-2318-14-62
|View full text |Cite
|
Sign up to set email alerts
|

An interprofessional nurse-led mental health promotion intervention for older home care clients with depressive symptoms

Abstract: BackgroundDepressive symptoms in older home care clients are common but poorly recognized and treated, resulting in adverse health outcomes, premature institutionalization, and costly use of health services. The objectives of this study were to examine the feasibility and acceptability of a new six-month interprofessional (IP) nurse-led mental health promotion intervention, and to explore its effects on reducing depressive symptoms in older home care clients (≥ 70 years) using personal support services.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 106 publications
3
59
0
8
Order By: Relevance
“…It has been well demonstrated that naïve nurses, including both those who are generally and mental health trained, are competent at delivering behavioural and cognitive behaviour therapies in a range of medical settings, mostly for depressive symptoms (Ekers et al, 2013a,b;Feng et al, 2012;Gega et al, 2007;Hendriks et al, 2014;Markle-Reid et al, 2014) but this study is the first to suggest superiority of nurses over other professional disciplines, including psychologists. The main limitation of the study is that the patients were not randomised to the therapists and so there could be confounding factors.…”
Section: Discussionmentioning
confidence: 79%
“…It has been well demonstrated that naïve nurses, including both those who are generally and mental health trained, are competent at delivering behavioural and cognitive behaviour therapies in a range of medical settings, mostly for depressive symptoms (Ekers et al, 2013a,b;Feng et al, 2012;Gega et al, 2007;Hendriks et al, 2014;Markle-Reid et al, 2014) but this study is the first to suggest superiority of nurses over other professional disciplines, including psychologists. The main limitation of the study is that the patients were not randomised to the therapists and so there could be confounding factors.…”
Section: Discussionmentioning
confidence: 79%
“…Multiple papers identified manageable workloads influenced nursing optimisation. Insufficient time to provide quality care was an optimisation barrier (Armstrong‐Stassen & Cameron, ; Cockerill et al, ; Denton, Zeytinoglu, Davies, & Hunter, ; Doran et al, ; Kaasalainen, Brazil, et al, ; Markle‐Reid et al, ; VON Canada, ; Williams, ). Specifically, healthcare restructuring (shifting acute care delivery from hospital to community) resulted in heavier workloads and increasingly complex patients receiving home care (Denton, Zeytinoglu, & Davies, ; Denton et al, ; Williams, ).…”
Section: Resultsmentioning
confidence: 99%
“…Since education typically produces generalists (Canadian Nurses Association, ), there is a need for orientation and access to standardised, ongoing training to fulfill HCN roles such as: case management, outcomes management, research, specialised technologies, program development and mental health promotion (Canadian Nurses Association, ; Dash, ; Home Care Sector Study Corporation, ; Kaasalainen et al, ; AETMIS, ; Lorimer, ; Markle‐Reid et al, ). Insufficient specialised orientation to manage increasingly complex work led to inappropriate assignments (VON Canada, ), workplace stress, absenteeism and burnout (Home Care Sector Study Corporation, ; Zeytinoglu & Denton, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has demonstrated that multiple barriers exist to intervention delivery in HHC interventions due to the complexity of the home environmental as well as the changing social milieu (Liebel, Friedman, Watson, & Powers, 2009;Markle-Reid et al, 2014). For example, one study (Nicolaides-Bouman et al, 2007) found that patients were less likely to engage in collaborative self-care management with nurses when there were contextual challenges such as unsafe home environments or cognitive decline.…”
Section: Discussionmentioning
confidence: 99%